If it's not what You are looking for type in the equation solver your own equation and let us solve it.
g(-1/3)=-1/3+2
We move all terms to the left:
g(-1/3)-(-1/3+2)=0
We multiply parentheses
-1g^2-(-1/3+2)=0
We get rid of parentheses
-1g^2-2+1/3=0
We multiply all the terms by the denominator
-1g^2*3+1-2*3=0
We add all the numbers together, and all the variables
-1g^2*3-5=0
Wy multiply elements
-3g^2-5=0
a = -3; b = 0; c = -5;
Δ = b2-4ac
Δ = 02-4·(-3)·(-5)
Δ = -60
Delta is less than zero, so there is no solution for the equation
| k/4-16=-14 | | 2-n/2=3n+16 | | |2x-6|-10=8 | | 3x5=4+x | | 7x-98=-9x+50 | | 7x+4(x15)=-181 | | 18x+27=81 | | x/8+1=3 | | 5/6=n24 | | 5x+55=2x+100• | | -16=-3x+-6 | | 2.5x10(-15)=3.9x10(26) | | -5x+1/2x-4=-13 | | 11x-28=7x-8 | | 18g-(-3g)=105 | | F(-5)=x^2-2x-7 | | 4x+2x+9=0 | | 5+3y+y=45 | | y-5.6=-3.5 | | (2x+1)^2-6=0 | | 47(2x)=94 | | -28=f/7-34 | | (2x+1)^2=6 | | 5(2x+1)^2-30=0 | | 9(2m-3)^2+8=449 | | 8-4d=20 | | 4x-12=2x+15 | | 5(2x+1)^2=30 | | 1x−15=4x−3 | | 12=j/4+9 | | -3(w+2)=2(w+6+7 | | n,n+7=8+n |